An Empire For Our Times? A Discussion of Peter Wilson's The Holy Roman Empire: A Thousand Years of Europe's History. Issue 4 (29th December 2017) - Unknown
Abstract : In the two centuries since its dissolution in 1806, the Holy Roman Empire has usually been viewed as an antiquated relic of the medieval past, a dysfunctional polity that hindered Germany's development into a modern, liberal nation-state. In the wake of its demise, a chorus of famous intellectuals and statesmen—including Voltaire, James Madison, Johann Wolfgang von Goethe, Leopold von Ranke, and Heinrich von Treitschke—derided the Empire as a "monstrosity" hampered by outmoded institutions and backward policies. More recently, in the wake of World War II and the Holocaust, advocates of the so-called Sonderweg thesis blamed the Empire for Germany's belated unification and for the Germans' supposedly "authoritarian" bent. In Heart of Europe [the American title of the study—Ed.], a bold and sweeping account of the Holy Roman Empire's thousand-year history, Peter Wilson sets out to supplant these anachronistic interpretations by explaining "what it was, how it worked, why it mattered, and its legacy for today" (5). With this important book, the best single-volume history of the Holy Roman Empire currently available, Wilson succeeds in answering these fundamental questions and provides fascinating insights into European politics from the early Middle Ages to the present. I would like to focus first on what I see as Wilson's most significant contributions to the existing scholarship on the Empire, and then examine how he treats the Protestant Reformation as a case study of the merits (and drawbacks) of his approach.